2012
DOI: 10.1007/s00428-012-1206-2
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiated peripheral chondrosarcoma: a clinicopathologic, immunohistochemical, and molecular analysis of four cases

Abstract: Peripheral dedifferentiated chondrosarcoma (DCS) is an exceedingly rare aggressive surface bone neoplasm in which a high-grade sarcoma arises within an osteochondroma. Four such examples were identified in our files, representing 11.1% of all DCS treated at our hospital in the years 1995-2010, and were the object of the present study. The patients were two men and two women ranging in age between 30 and 64 years, with tumors located in the pelvis (n 0 2), in the scapula (n 0 1), and the tibia (n 0 1). Radiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Prior studies have identified TP53 mutation and/or protein overexpression in DDCS, although only in a few tumors and without separate study of both components. 10,15,16,31,32 The current study confirms that inactivating mutations in TP53 are common in DDCS and, in a subset of cases, the TP53 mutation is restricted to the dedifferentiated nonchondrogenic component. In the subset of cases in which TP53 mutations were present in both components, the alteration was subclonal in the chondrogenic components relative to the IDH1/2 alteration.…”
Section: Discussionsupporting
confidence: 81%
“…Prior studies have identified TP53 mutation and/or protein overexpression in DDCS, although only in a few tumors and without separate study of both components. 10,15,16,31,32 The current study confirms that inactivating mutations in TP53 are common in DDCS and, in a subset of cases, the TP53 mutation is restricted to the dedifferentiated nonchondrogenic component. In the subset of cases in which TP53 mutations were present in both components, the alteration was subclonal in the chondrogenic components relative to the IDH1/2 alteration.…”
Section: Discussionsupporting
confidence: 81%
“…This finding diverges from the largest reports of central dedifferentiated chondrosarcoma where MFH-like features comprised from 4% to 22% of the total cases, and osteosarcoma-like characteristics usually dominate [2, 3, 16, 28]. Other reports have documented a rate of MFH-like histologic subtypes greater than 50% in the peripheral form of dedifferentiated chondrosarcoma, indicating that the peripheral form may have a predilection for this morphology [7, 12, 15]. …”
Section: Discussionmentioning
confidence: 59%
“…We reviewed previous reports about peripheral dedifferentiated CS, excluding additional reports from the same institution (Table I) [5][6][7][8][9][10][11][12] . Overall, 28 cases appeared in the English literature.…”
Section: Discussionmentioning
confidence: 99%